Experiences of the SICAP Research Seeding in the Development of Soft Skills (2017)
The research seeding in applied sciences (SICAP) has the determination to improve specific skills but also develop soft skills in the Mechanical and Electrical Engineering students from the Pascual Bravo University Institution. One of that specific skills is machine and product design. On this occasion are shown activities from mechanical conceptual design resolved by work groups, following some elements from Cross Methodology (only the stages tree of objective, Functional analysis, Morphological diagram and weighted objectives) mixed whit traditional research methodologies, all joint whit activities that allow to conduct experiments, make decisions, team work, time management, develop communications and creative skills. The specific skills were evaluated by the finished of the conceptual design but the acquisition of soft skills was evaluated using a survey, as result the competences that most favor the methodology for designing prototypes in the SICAP research seedling are decision-making and communication with the work group and between colleagues.